Predictive Business Analytics: The Way Forward - Kumar, Naresh; Dadhich , Manish (Gyan Management Journal, 2014)
This paper delves the various aspect and application of predictive analytical tools because it provides greater transparency, and can find and analyze past and present trends, as well as the hidden nature of data. However, past and present insight and trend information are not enough to be competitive in business. Business organizations need to know more about the future, and in particular, about future trends, patterns, and customer behavior in order to understand the market better so at this juncture understanding the predictive business analytics is the need of the hour to predict the future outcome. Traditional analytics help gain insight for what was right and what went wrong in decision-making. Today’s tools merely provide rear view analysis. However, one cannot change the past, but one can prepare better for the future and decision makers want to see the predictable future, control it, and take actions today to attain tomorrow’s goals.